Muatan HOTS pada Pembelajaran Tematik Materi IPA Kelas 5 Sekolah Dasar - Maratul Qiftiyah (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
This study aims to describe the content of higher order thinking skills in the fifth-grade science material on the theme of animal and human movement organs in terms of HOTS aspects. This type of research is a descriptive type of content analysis. The main source of this research is thematic books for grade V. The data were analyzed descriptively qualitatively and quantitatively. Analysis of the data of this research through three stages, namely data condensation, data display, and drawing conclusions or verification. The data collection technique in this study was reading and recording HOTS content in terms of its aspects. The results of this study found that the science material presents higher-order thinking skills at the C4-C6 level which refers to Bloom's revised taxonomy. Student thematic books also provide material to foster critical/creative thinking skills and reasoning abilities. HOTS aspects as critical and creative thinking dominate each sub-theme, while HOTS aspects as problem solving as well as the transfer of knowledge still need to be synchronized again.